Analisis Faktor Pendidikan dan Kesehatan terhadap Indeks Kebahagiaan Masyarakat Indonesia: Perspektif Psikologi Positif - Agustina Nicke Kakiay (Jurnal Ilmu Sosial dan Humaniora, 2026)
Happiness is an important indicator of subjective well-being and has become a central topic in positive psychology. This study aims to analyze the relationship between education and health factors and the Happiness Index in Indonesia using secondary data from the Central Bureau of Statistics (BPS) in 2021. The study employed a quantitative explanatory approach with a sample of 34 provinces selected through total sampling. The dependent variable was the Happiness Index, while the independent variables included Expected Years of Schooling, Mean Years of Schooling, and Life Expectancy. Data were analyzed using descriptive statistics and multiple linear regression with IBM SPSS Statistics 26. The results indicated that Expected Years of Schooling, Mean Years of Schooling, and Life Expectancy did not have a statistically significant relationship with the Happiness Index, either simultaneously or partially. The coefficient of determination showed that the model explained only a small proportion of the variation in the Happiness Index, indicating that other factors beyond education and health may play a more substantial role in determining happiness. These findings suggest that improving public happiness requires a broader approach that considers social, economic, and psychological dimensions in addition to education and health.